Estimation of Uranium Concentration in Urine Samples of Three Age Groups of Healthy Individuals in Najaf Governorate Using CR-39 and LR-115 Solid State Detectors - Abbas, Samia K.; Hussain, Hayder S.; Saleh, Dhuha S. (Iraqi Journal of Science, 2022)
Uranium concentration was estimated in urine samples of three age groups, G1≤ 30 years, n=28, G2 age range of 31-40 years, n=28, and G3 of age > 40 years, n=32, using two types of detectors CR-39 and LR-115 solid-state nuclear track detector (SSNTD) for results comparison. Results showed that uranium mean level values for CR-39 were 1.961 ±0.08 µg/L, 1.810 ±0.09 µg/L and 1.814 ±0.076 µg/L for G1, G2 and G3 respectively, while the mean values of uranium concentration using LR-115 were 0.972 ±0.07 µg/L, 0.922 ±0.07 µg/L and 1.018 ±0.08 µg/L in G1, G2 and G3 respectively, with significant statistical difference between the results of CR-39 and LR-115 for each age group. Mean level values for females was 2.023± 0.09 µg/L and 1.813± 0.05 µg/L for males using CR-39 and it was 1.105± 0.09 µg/L for females and 0.933± 0.04 µg/L for males using LR-115, with significant statistical difference between results for each gender.It was concluded that G1 ≤ 30 years have the highest uranium pollution, noting that females were more polluted with uranium than males.